Caracterización de las nuevas empresas internacionales de los sectores manufactureros tradicionales - Cantarero Sanz, Santiago (2013)
The main objective of this study was to study the characteristics of the New International Business (NIS) or Born-Global in a sample of 81 SMEs belonging to the Spanish textile sector. This is descriptive analysis regarding the location, the subsector of activity, size, economic performance and internationalization strategy implemented by the NEI (2005-2009).The results identified three groups of NIS: export, import and export-import. The group of companies that makeup the largest importers and are associated with smaller companies. The exporters appear to be related more to low techsub-sectors while more internationally committed are those with a higher dimension. Regarding the location not detected any evidence of territorial pattern. Finally, among firms internationalized in the time period analyzed, it is also noteworthy that the economic performance of these is higher among importers. This study provides information on why the same country and same industry some companies decide shortly be created to assume certain levels of risk, engaging in operations engaged in foreign markets while others do not. It also participates in the debate on the competitiveness of manufacturing companies.